Fingerprinting de cocaína : um estudo do perfil químico no estado do Espírito Santo - Souza, Lindamara Maria (2014)
Cocaine is a central nervous system (CNS) stimulant drug that causes psychological dependence. The duration of its effects depends on the form consumed (salt, e.g. cocaine hydrochloride, or base, e.g. crack) and on the mode of administration (snorting, smoking or injecting). Cocaine is defined as a tropanic alkaloid present in its structure by the tropane core. Despite its defined composition, aiming to increase the final amount of drug, illicit market applies a wide variety of diluent chemicals such as benzocaine, lidocaine, caffeine, procaine, among others. This project was divided into three chapters dedicated to: i) evaluating colorimetric, ie, the Scott test, using infrared spectroscopy with Fourier transform using Attenuated Total Reflection accessory (ATR-FTIR). Seventeen chemical additives were evaluated, which provided four false positives (promethazine, lidocaine, powdered milk and yeast). As the Scott test is performed and combined with spectroscopic techniques such as ATR-FTIR and chemometrics, conclusive results are obtained and can be used for routine forensic laboratories. ii) organic chemical profile of samples seized in the year 2012 in the months from January to July were analyzed using gas chromatography coupled to a quadrupole mass spectrometer (GC-MS) was studied. In this chapter, 101 samples were analyzed in full scan mode and 83 of these used to construct a model of principal component analysis (PCA). The main adulterants found were lidocaine, phenacetin and caffeine. Additionally, cocaine, lidocaine and caffeine were quantified from the selected ion monitoring (SIM), and their values of linearity, limits of detection and quantification determined. iii) samples of cocaine seized by the Civil Police were classified according to the time (2008, 2009, 2010, 2011 and 2012) and the location of apprehension (in relation to the four geographical regions of the state) using the technique of GC-MS associated with multivariate analysis (PCA), where a total of 512 samples were investigated.